Exploitation, technology and function of plant resins in Oceania: molecular analysis of ethnographic museum artefacts and the implications for archaeological resin analysis - Bradshaw, FG (2019)
Oceania has an extremely diverse and unique flora that includes many endemic species of restricted geographic range. This flora comprises coniferous, deciduous, and monocot plants and trees that include many resin-producing species. Plant resins have a long ethnobotanical history in Indigenous Oceania, as is recognised by some rare archaeological finds as well as a rich ethnographic record. In this study, gas chromatography-mass spectrometry (GC-MS) has been employed to chemically investigate resins of ethnobotanical importance in Oceania including Australia. A total of 173 samples of resinous material from ethnographic artefacts, currently held in museums, was analysed alongside botanically identified reference materials from in and around the area. The aim was to both contribute to our understanding of the role of resins in Indigenous Oceania, and provide a framework for efficiently and effectively analysing valuable resinous archaeological finds from the region.